Deep-ultraviolet light-emitting diodes with external quantum efficiency higher than 20% at 275 nm achieved by improving light-extraction efficiency - Takano, Takayoshi; Mino, Takuya; Sakai, Jun; Noguchi, Norimichi; Tsubaki, Kenji; Hirayama, Hideki (Applied physics express, 2017)
Enhancing the light-extraction efficiency is the key issue for realizing highly efficient AlGaN-based ultraviolet light-emitting diodes (UV-LEDs). We introduced several features to improve the light extraction: a transparent AlGaN:Mg contact layer, a Rh mirror electrode, an AlN template on a patterned sapphire substrate, and encapsulation resin. The combination of the AlGaN:Mg contact layer and the Rh mirror electrode significantly improved the output power and the external quantum efficiency (EQE) of UV-LEDs. By introducing the aforementioned features, a maximum EQE of >20% at an emission wavelength of 275 nm and a 20-mA direct current was achieved.